ANALISIS KINERJA KEUANGAN PT. BANK SINARMAS Tbk, UNIT USAHA SYARIAH - Suwarni Suwarni; Karona Cahya Susena; Wika Gusti (UNIVED Press, 2018)
Suwarni, Karona Cahya Susena, Wika Gusti Halimah; The purpose of this study is to determine and measure the level of financial performance of PT. Bank Sinarmas Tbk, Sharia Business Unit Year 2014-2016. Sharia business with financial ratios are Liquidity ratio, Solvency ratio, and Profitability.The result of this study shows that Cast Ratio from 2014 until 2016 is 47,57%, 219,70% and 312,21%. From Loan Deposito Ratio (LDR) from 2014 until 2016 are 81,22%, 72,73% and 17,06%. From Capital Adequacy Ratio perspective, in 2014 until 2016 the values are 125,06%, 362,18% and 2.285%, meanwhile from Debt to Equity perspective, in 2014 until 2016 the values are 84,27%, 29,84% and 12,88%. By using BOPO in 2014 until 2016 the values are 65,83%, 109,21% and 155,49%. From Return on Assets perspective, in 2014 until 2016 the values are 1,31%, 0,10% and1,64%. Meanwhile from the Return on Equity in 2014 until 2016 values are 2,41%, 0,26%, and 1,85%.Key Words: Liquidity Financial Report ratio, Solvability, Profitability, Financial Performance.